2008
DOI: 10.4103/0973-3930.44079
|View full text |Cite
|
Sign up to set email alerts
|

Educational program for patients with type-1 diabetes mellitus receiving free monthly supplies of insulin improves knowledge and attitude, but not adherence

Abstract: BACKGROUND:Though patients attending a diabetic clinic in a tertiary care hospital were given free monthly supplies of insulin, it was found that their glycemic control was poor.SETTINGS AND DESIGN:A prospective interventional study was carried out at the outpatient clinic in a tertiary care hospital.AIMS:To evaluate the effectiveness of a six month educational interventional program on the knowledge, attitude and practices (KAP) of type-1 diabetic patients receiving free monthly supplies of human insulin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“… 31 Thus, many researchers want to evaluate the education of patients regarding T1DM. 32 , 33 They conclude that education is needed to control T1DM in children, adolescents, and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 Thus, many researchers want to evaluate the education of patients regarding T1DM. 32 , 33 They conclude that education is needed to control T1DM in children, adolescents, and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, educating patients with T1DM is essential to maintain patient adherence and its effect on patient QoL. 32 However, the study evaluating the efficacy of education to the improvement of the PedsQL score has not yet been conducted. This study found that QoL improvement was significant in all groups (parents and children).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in South India reported that there is a poor knowledge on insulin use among the diabetes patients who were on insulin. [1013] Injection technique is critical to the therapeutic success of insulin and is highly operator-dependent. The correct administration technique will help in reducing the HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Health education interventions were found to improve the knowledge and attitude domains profoundly; however, the improvement in the practice domain was relatively less. [10] One of the reasons could be that most patient education interventions did not provide hands-on training to the patient.…”
Section: Introductionmentioning
confidence: 99%